Loving the Sport, Loving the Self: Devotion and Defiance in Furia - Wendy J. Glenn (Literature)
In the world of sports today, young people have access to models of women athletes who seem to have it all, women whose actions push on gendered assumptions of love and the associated roles of women as sacrificial and subservient. And yet, young people, particularly young girls, wanting to navigate their worlds in ways that challenge conventional love, do not have the same power and privilege given their gender, age, and lack of financial autonomy. The young adult novel Furia invites young readers to evidence an adolescent character whose love of sport serves as a form of liberation from social constraints in a way that likely feels more resonant and doable, more real somehow. The protagonist’s engagement with and dedication to sport invite complications of ideological assumptions about love, particularly gendered narratives that position girls and women as bound by devotion This paper draws upon the youth lensand methods of critical context analysis to better understand how the protagonist is positioned as an athlete and a young woman and to offer interpretative thinking that explores how this title can help us (and young readers) think about love through the lens of sport.